TEACHING EFL WRITING USING GOOGLE DOCS TO PROVIDE FEEDBACK - Wibowo, Annindita Putri (LLT Journal: A Journal on Language and Language Teaching, 2021)
An innovative teaching and learning process in a class is essential to provide a meaningful and successful learning experience. Peer feedback evaluating the other students’ writing helps them check, correct errors in writing, and analyze the mistakes to lead to a better understanding and a good improvement. Thus, this study is conducted to observe Google Docs’ use with peers’ feedback for having an innovative teaching and learning process in EFL writing class. 10 EFL students, including male and female from one of the public universities in Central Java, Indonesia studying in the 5th semester are surveyed via non-probability sampling and asked for their participation in this study. The ten students chosen will be interviewed regarding the activities using Google Docs in their article writing class such as commenting and revising after they get the feedback and their reflection of these activities. The results of this study found that Google Docs providing feedback helps students write an article, although they also found some challenges. This study suggests that the lecturers' guidance and perspective are needed in feedback activity during the writing class to have a better and more effective learning process.